“Pra não dizer que não falei das flores”: um estudo sobre mulheres rurais e medicalizações - Silveira, Mariana Paixão da (2020)
This research investigates the processes of medicalization and how they are derived from the lives of rural women in the State of Bahia. In order to analyze the relationships between women, rural territories and medications, this study is going to be guided by the experience of care provided to women living in rural areas and a consequent observation of the indiscriminate uses of benzodiazepine medications (popularly known as tranquilizers) in spaces. Based on women's narratives about the ways of life and health in their territories, we seek to promote the exercise of critical reflections on the developments of the processes of medicalization in spaces. The methodology used is of a qualitative nature, inspired by participatory action research and it is going to be have as a procedure the analysis of field records generated during the insertion period in rural territories, from the perspective of critical social psychology and feminist epistemology. The processes of medicalization of women's lives is going to be discussed based on the health-disease conditions and the axes: violence, services and health and work professionals